2019
DOI: 10.1017/mdh.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the Test Tube: The Birth of IVF on British Television

Abstract: The birth of Louise Brown, the world’s first ‘test-tube baby’, has come to signify the moment at which technologically assisted human reproduction became a re ality. This was a highly mediated and visible reality, as this article explores through the example of a British television documentary about Louise Brown broadcast when she was just six weeks old, ‘To Mrs Brown… A Daughter’ (Thames Television, 1978). In the article, I discuss the programme alongside data from an interview with its producer, Peter Willia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…There are more than 70 articles that described the birth of first test tube baby, Louis brown and the scientists who made it possible underwent great criticism initially. [4,5] The history of human invitro fertilization has been recently reviewed [3] and it is reported that the first pregnancy which ended up in early embryo demise was in Melbourne , Australia and the procedure was performed in 1973 by Prof. Carl Wood and John Leeton. In 1976, Patrick Christopher Steptoe, Gynaecologist and Robert Geoffrey Edwards, a British physiologist published a report of ectopic pregnancy following transfer of a morula.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 70 articles that described the birth of first test tube baby, Louis brown and the scientists who made it possible underwent great criticism initially. [4,5] The history of human invitro fertilization has been recently reviewed [3] and it is reported that the first pregnancy which ended up in early embryo demise was in Melbourne , Australia and the procedure was performed in 1973 by Prof. Carl Wood and John Leeton. In 1976, Patrick Christopher Steptoe, Gynaecologist and Robert Geoffrey Edwards, a British physiologist published a report of ectopic pregnancy following transfer of a morula.…”
Section: Discussionmentioning
confidence: 99%
“…This choice does not disregard the biogenetic connection but deemphasizes it to help support the vision of kin that they are helping to create 117 . The idea that motherhood and kinship are culturally constructed has been argued by Critical Kinship scholars (Dow 2019;Franklin 1997;Teman 2010;Weiss 1994), problematising the assumptions within psychosocial studies that postulate that a lack of maternal instinct or mother-child bonding is due to psychological issues (Alhusen 2008;Ciccarelli 1997, 2;Condon andCorkindale 1997 Resnick 1990;Teman 2008). Jacobson (2016, 5) writes:…”
Section: The Polarisation Of and Discomfort With Traditional Surrogacymentioning
confidence: 99%
“…Yet the main resource is the vast printed (and increasingly digitized) record, from scientific journals and conference proceedings to glossy magazines and tabloid newspapers, and to a lesser extent television and radio broadcasts, interpretation of which has barely started (but see Van Dyck, 1995;Turney, 1998, pp. 166-187;and Dow, 2017and Dow, , 2019aand Dow, , 2019b; for an exemplary study, Nathoo, 2009;and for a general review, Hopwood et al, 2015). Analysis could, among many other things, bring several more patients from the Oldham programme into the picture (e.g., Bedford, 1970;New 'test tube' mother says: never again, 1970).…”
Section: From Personality To Public Figurementioning
confidence: 99%